Phosphorylation of NuMA by Aurora‐A kinase in PC‐3 prostate cancer cells affects proliferation, survival, and interphase NuMA localization. Issue 4 (18th February 2013) - Toughiri, Raheleh; Li, Xiang; Du, Quansheng; Bieberich, Charles J.
Abstract Aurora‐A is a serine/threonine kinase that has oncogenic properties in vivo. The expression and kinase activity of Aurora‐A are up‐regulated in multiple malignancies. Aurora‐A is a key regulator of mitosis that localizes to the centrosome from the G2 phase through mitotic exit and regulates mitotic spindle formation as well as centrosome separation. Overexpression of Aurora‐A in multiple malignancies has been linked to higher tumor grade and poor prognosis through mechanisms that remain to be defined. Using an unbiased proteomics approach, we identified the protein nuclear mitotic apparatus (NuMA) as a robust substrate of Aurora‐A kinase. Using a small molecule Aurora‐A inhibitor in conjunction with a reverse in‐gel kinase assay (RIKA), we demonstrate that NuMA becomes hypo‐phosphorylated in vivo upon Aurora‐A inhibition. Using an alanine substitution strategy, we identified multiple Aurora‐A phospho‐acceptor sites in the C‐terminal tail of NuMA. Functional analyses demonstrate that mutation of three of these phospho‐acceptor sites significantly diminished cell proliferation. In addition, alanine mutation at these sites significantly increased the rate of apoptosis. Using confocal immunofluorescence microscopy, we show that the NuMA T1804A mutant mis‐localizes to the cytoplasm in interphase nuclei in a punctate pattern. The identification of Aurora‐A phosphorylation sites in NuMA that are important for cell cycle progression and apoptosis provides new insights into Aurora‐A function. J. Cell. Biochem. 114: 823–830, 2013. © 2012 Wiley Periodicals, Inc.